Differences in hospital length of stay between neonates exposed to buprenorphine versus methadone in utero: A retrospective chart review. Issue 2 (17th July 2018) - Fernandez, Sarah; Bruni, Teresa; Bishop, Lisa; Turuba, Roxanne; Olibris, Brieanne; Jumah, Naana Afua
Abstract: Introduction: Neonatal abstinence syndrome is a growing concern in neonatal intensive care units in rural and remote settings. Methods: A retrospective chart review was conducted of 180 mother–infant dyads born with in utero exposure to buprenorphine (n=60), methadone (n=60) or to other opioids (n=60) to determine neonatal length of stay in hospital, number of days on morphine, day of life of initiation of morphine and the need for phenobarbital. Results: The length of stay in hospital for neonates was 5.8 days shorter (95% confidence interval [CI] 6.1 to 8.5 days) for buprenorphine exposure in utero compared to methadone (P=0.001). For neonates requiring treatment for Neonatal abstinence syndrome, those with in utero exposure to buprenorphine required 6.1 fewer days (95% CI 2.5 to 9.7) of treatment with morphine then those exposed to methadone (P<0.0005). There were no statistically significant differences in day of life of initiation of morphine therapy for each of the study groups. The proportion of neonates requiring adjuvant therapy with phenobarbital was statistically significantly higher in neonates exposed to methadone in utero than either buprenorphine or illicit opioids (P<0.0005). Conclusions: Retrospective data suggest that neonates with in utero exposure to buprenorphine experience a shorter length of stay in hospital, fewer days of treatment with morphine for neonatal abstinence syndrome, and less use of phenobarbital than neonates exposed in utero to methadone. This suggests that Ontario provincial guidelines should be updated to recommend buprenorphine as first line for replacement therapy in pregnancy.